2020
DOI: 10.1038/s41598-020-59199-6
|View full text |Cite
|
Sign up to set email alerts
|

Motor representations underlie the reading of unfamiliar letter combinations

Abstract: Silent reading is a cognitive operation that produces verbal content with no vocal output. one relevant question is the extent to which this verbal content is processed as overt speech in the brain. to address this, we acquired sound, eye trajectories and lips' dynamics during the reading of consonantconsonant-vowel (ccV) combinations which are infrequent in the language. We found that the duration of the first fixations on the CCVs during silent reading correlate with the duration of the transitions between c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
6
0
Order By: Relevance
“… 108 A recent eye-tracking study found a correlation between ocular dynamics in silent reading of infrequent letter strings and articulatory dynamics in reading aloud the same letter strings, suggesting the involvement of motor representations in the silent reading of unfamiliar letter strings. 109 Future research should examine the relationship between impaired motor-phonological processing and performance on reading tasks that do not require overt speech production. It is also notable that we contrasted performance reading pronounceable pseudowords versus regular words.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 108 A recent eye-tracking study found a correlation between ocular dynamics in silent reading of infrequent letter strings and articulatory dynamics in reading aloud the same letter strings, suggesting the involvement of motor representations in the silent reading of unfamiliar letter strings. 109 Future research should examine the relationship between impaired motor-phonological processing and performance on reading tasks that do not require overt speech production. It is also notable that we contrasted performance reading pronounceable pseudowords versus regular words.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion size is in mm 3 . WAB AQ represents the Aphasia Quotient from the ‘Western Aphasia Battery—Revised’, 109 which measures aphasia severity: 0–25 = very severe, 26–50 = severe, 51–75 = moderate, 76+ = mild.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated both the left and right TMJs in 57 patients (36 women and 21 men) using computed tomography (CT) (Aquilion 64™, Canon Medical Systems Corporation, Tochigi, Japan) before and after IVRO. This study utilized cases and methods that we have previously published 9 .…”
Section: Methodsmentioning
confidence: 99%
“…After IVRO, the medial pterygoid muscle was almost detached from the proximal segment in all cases. The distal fragment of the mandible was placed in the planned postsurgical position and stabilized using rigid MMF and a splint in the maxillary dental arch 9 . Rigid interosseous fixation was not performed in any of the patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation